Expanding the Circular Life of a Garment Proposing a Circular Concept for the Clothing Company EmmaMalena - Minborg, Elis (My University, 2023)
Summary Textiles are an environmental problem causing water use, pollution, greenhouse emissions and great landfills. One way to reduce global textile impact is through increased circularity, meaning that the textile is used as much as possible through methods such as passing it on to several people or re-making the material into new items before disposal. Although many people are willing to participate in a circular economy by donating used clothes, these garments can still face disposal instead of being re-used. Improvements in production standards, infrastructure, and user motivation is required for a successful re-utilization of the products. This thesis was done in cooperation with EmmaMalena, a clothing company from Käringön Sweden, and representatives from the Chalmers Department of Industrial & Material Science. The purpose was to find a solution where the clothing company can increase circularity of their garments in a way that is attractive for their customers and helps strengthen their brand. Field studies, data collection from existing personas, and in-depth interviews were conducted to explore existing user needs and requirements. A new concept was created by ideation and workshops together with EmmaMalena. The design Toolkit, Use2Use, supported and structured the development process. Furthermore, the motivational design tool Octalysis was utilized to increase the likelihood of users successfully performing the required actions. The final concept consisted of a pilot project designed to collect disused EmmaMalena clothing and resell them in-store. It further included a branding concept called “Tångcirkeln” to be implemented in-store, on garments, and online to symbolize and highlight EmmaMalena's sustainability efforts. Moreover, Tångcirkeln is also a name of a loyalty program where people provide action in a group for a higher cause. One specific common-cause solution is to participate in replanting eelgrass. Eelgrass acts as a carbon sink, and keeps the local shores clear and diverse, making participation in replanting initiatives a suitable cause for all EmmaMalenas customer segments.This report's design process has further yielded a great number of concepts that can be implemented in Tångcirkeln in a long-term perspective.
Keywords: Circular, garment, textiles, clothing, environment, Use2Use, Octalysis, EmmaMalena, Chalmers, Tångcirkeln